Upscaling Ecotourism Initiatives: Case Study of Uttar Pradesh (Leadership, Education, Personality: An Interdisciplinary Journal, ISSN: 2524-6178, 2024)
The concept of sustainable development can be traced to the world conservation strategy published by the World Conservation Unit in 1980. India is one of those rare countries endowed with the resources that are essential to making the country a golden star on the eco-tourism map of the world. To maintain ecological balance and preserve the indigenous culture of the local people, the Ministry of Tourism and Culture Government of India has advocated a super segmentation of the tourism market in the Tourism Policy, 2002. In 2008, after an interactive Indo-Australian Intergovernmental Meeting on ecotourism, the Ministry of Tourism stepped up the preparation for promoting ecotourism. It widened its mandate of driving responsible tourism through all the sectors. Eco-tourism is non-wrenching and non-consumptive. This new wave of tourism has benefited the local communities, in particular, and the people and the planet in general. The other reason behind ecotourism gaining impetus includes a strong demand for customised travel post-COVID-19 pandemic, which has led to permanently altered consumer preferences. Blessed with abundant natural diversity, India is a potential global eco-tourist destination. From the dramatic deserts of Rajasthan to the lush green forest of Cherrapunji, from the blue beaches of south India to the snow-capped reaches of the Himalayas, it has established itself as the top favourite ecotourism destination throughout the decade.